PENGARUH SENAM DISMENORHEA TERHADAP PENURUNAN NYERI MENSTRUASI PADA MAHASISWA KEBIDANAN - Dartiwen Dartiwen (JURNAL KESEHATAN INDRA HUSADA, 2022)
Dysmenorrhea is pain that occurs during menstruation which can interfere with student learning activities. To reduce pain, non-pharmacological alternatives are carried out with dysmenorrhea exercise. The purpose of this study was to reveal something new, namely the effectiveness of dysmenorrhea exercise on reducing menstrual pain in midwifery students. This study is a quasi-experimental study with a pre-post test research design with a control group involving two groups, namely the intervention group of 19 people and the control group of 22 people. The sample in this study used the total population. The intervention group was given dysmenorrhea exercise twice a week for four weeks. Pain measurement using Numeical Rating Scale (NRS). Statistical test with mann whitney and chi – square. The results showed that in the intervention group there was a decrease in menstrual pain after doing dysmenorrhea exercise (p = 0.001). This study concludes that dysmenorrheal exercise is effective in reducing the intensity of pain during menstruation. For students who experience menstrual pain, it is recommended to do dysmenorrhea exercises instead of taking drugs that have side effects on body health.